Correction: Including population and environmental dynamic heterogeneities in continuum models of collective behaviour with applications to locust foraging and group structure. - PLOS Computational Biology Staff (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1011469.].